Costs and benefits of friendly boards during mergers and acquisitions - Schmidt, Breno (Journal of Financial Economics, 2015)
Finance theory predicts that board independence is not always in the shareholders׳ interest. in situations in which board advice is more important than monitoring, independence can decrease firm value. I test this prediction by examining the connection between takeover returns and board friendliness, using social ties between the CEO and board members as a proxy for less independent boards. I find that social ties are associated with higher bidder announcement returns when the potential value of board advice is high, but with lower returns when monitoring needs are high. The evidence suggests that friendly boards can have both costs and benefits, depending on the company׳s specific needs.